PALINOLOGIA DEL PALEOCENO DE CHUBUT. II. DIAGRAMAS POLINICOS (Ameghiniana, 2013)
The present paper deals with the pollen diagrams of several surface and subsurface sections of the Salamanca Formation. The diagrams of each section comprise three parts: 1) relation of pollen to palaeomicroplankton, 2) percentages of pollen groups (Classopollis, Saccites, Mono- Tricolpate, Porate, Tricolporate and Trilete-Monolete spores), 3) percentages of the most important species (those represented by more than 2 % in some of the horizons studied). Relations of species and groups to maxima and mínima of the palaemicroplankton are analyzed. In some sections (Bajada de Hansen, H-291) two maxima of palaeomicroplankton are distinsuished; they probably correspond to ingressions of the Atlantic waters towards the West. The top of the formation is regressive and the overlying Río Chico Formation (also of Palaeocene age) is entirely continental.